COMPARISON BAY LEAF (SYZYGIUM POLYANTHUM (WIGHT) WALP) EXTRACT WITH 400 MG AND 600MG DOSE ON NITRIT OXIDE CONCENTRATION IN DYSLIPIDEMIC PATIENTS - Otneil Karnianta, Dharma Lindarto & Santi Syafril (International Journal of Research Science and Management, 2020)
Introduction: Dyslipidemia is a risk factor for cardiovascular disease. Dyslipidemia is known to trigger damage to endothelial blood vessels so that the disruption of nitric oxide production. Nitric oxide in blood vessels acts as an antiaterosclerotic agent, vasodilator, and prevents platelet aggression. Bay leaf extract is reported to be efficacious in reducing cholesterol, triglyceride levels and can increase levels of nitric oxide. This study aims to compare the effects of bay leaf extract at a dose of 400 mg and 600 mg on nitric oxide levels in dyslipidemic patients. Method: Clinical trial research with a prospective design. The first group (n = 15) was given therapy with dose of 400mg and the second group (n = 15) was given 600mg which was chosen randomly selected randomly in double disguised. Before and after 30 days of treatment, lipid profile and nitric oxide were examined. Data were analyzed by T-dependent statistical test and Wilcoxon test using SPSS. Significant difference when p <0.05. Result: Nitric oxide levels before drug administration compared with after treatment. The results of the study found a decrease in group I (41.71 vs 46.62) mmol / L; p = 0.233) and group II ((39.89 vs 52.62) mmol / L; p = 0.006), statistically significant in group II. Increased levels of nitric oxide in group II were greater than group I (∆4.91 vs ∆12.73), and statistically significant; p = 0.001). Conclusion: The used of bay leaf extract (Syzygium polyanthum) 600 mg for 30 days increases nitric oxide levels greater than 400 mg, and is statistically significant.